Azathioprine-Induced Pericarditis in a Patient with Ulcerative Colitis - C David Simpson (Canadian Journal of Gastroenterology)
Inflammatory bowel disease is rarely associated with pericarditis but both sulfasalazine and the aminosalicylates have been known to cause this complication. To the author's knowledge this is the first reported case of acute pericarditis caused by azathioprine. It is believed that pericarditis is yet another potential manifestation of hypersensitivity to this drug.